Logics of art collection in confrontation: Monteiro Lobato and Anita Malfatti - Cruz, Benilton Lobato (Revista de Letras, 2018)
This paper proves that there were two logics of shock art collection from the effects of “Modern Painting Exhibition”, 1917. The publication of “The Purpose of Malfatti Exhibition”, Monteiro Lobato, headed the first logical art collection, which fed the Romanticism triad, Nationalism and Naturalism. The other side, in turn, initiated by São Paulo artist, questioning the role of mimetic action in the new art course, would point out the need to review the historical foundation of this proposal. This research proves, in fact, that in both lines had a defensive posture, behavior that outlines the future of each of these views. The term “logic of Art Collection”, created by Boris Groys (2004) in order to expose the important role of the museum in the acceptability of the new, settles on the change wrought by the museum itself as the focus of the art of reading. And from this angle, this article proves that the two aesthetics are accepted by the literature, the favorable field to understanding the interference of museum space in the definition of art direction.